Hemispherectomy Procedure in Proteus Syndrome - GUNAWAN, Prastiya Indra; LUSIANA, Lusiana; SAHARSO, Darto (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Gunawan PI, Lusiana L, Saharso D. Hemispherectomy Procedure in Proteus Syndrome. Iran J Child Neurol.Summer 2016; 10(3):86-90 Objective Proteus syndrome is a rare overgrowth disorder including bone, soft tissue, and skin. Central nervous system manifestations were reported in about 40% of the patients including hemimegalencephaly and the resultant hemicranial hyperplasia, convulsions and mental deficiency. We report a 1-month-old male baby referred to Pediatric Neurology Clinic Soetomo Hospital, Surabaya, Indonesia in 2014 presented recurrent seizures since birth with asymmetric dysmorphic face with the right side larger than the left, subcutaneous mass and linear nevi. Craniocervical MRI revealed hemimegalencephaly right cerebral hemisphere. Triple antiepileptic drugs were already given as well as the ketogenic diet, but the seizures persisted. The seizure then was resolved after hemispherectomy procedure. References Beachkofsky TM, Sapp JC, Biesecker LG, Darling TN. Progressive overgrowth of the cerebriform connective tissue nevus in patients with Proteus syndrome. J Am Acad Dermatol 2010;63:799-804. Biesecker L. The challenges of Proteus syndrome: diagnosis and management. Eur J Hum Genet 2006;14:1151-7. Yamatogi Y, Ohtahara S. Early-infantile epileptic encephalopathy with suppression-bursts, Ohtahara syndrome; its overview referring to our 16 cases. Brain Dev 2002;24:13-23. Bastos H, da Silva PFS, de Albuquerque MAE, Mattos A, Riesgo RS, Ohlweiler L, et al. Proteus syndrome associated with hemimegalecephaly and Ohtahara syndrome: Report of two cases. Seizure 17(4):2008. Turner JT, Cohen MM, Jr., Biesecker LG. Reassessment of the Proteus syndrome literature: application of diagnostic criteria to published cases. Am J Med Genet A 2004;130A:111-22. Cohen MM, Jr. Proteus syndrome: clinical evidence for somatic mosaicism and selective review. Am J Med Genet 1993;47:645-52. Bilkay U, Tokat C, Ozek C, Gundogan H, Erdem O, Gurler T, et al. Proteus syndrome. Scand J Plast Reconstr Surg Hand Surg 2003;37:307-10. Biesecker LG, Happle R, Mulliken JB, Weksberg R, Graham JM, Jr., Viljoen DL, et al. Proteus syndrome: diagnostic criteria, differential diagnosis, and patient evaluation. Am J Med Genet 1999;84:389-95. Caraballo R, Bartuluchi M, Cersosimo R, Soraru A, Pomata H. Hemispherectomy in pediatric patients with epilepsy: a study of 45 cases with special emphasis on epileptic syndromes. Childs Nerv Syst 2011;27:2131-6. Moosa AN, Gupta A, Jehi L, Marashly A, Cosmo G, Lachhwani D, et al. Longitudinal seizure outcome and prognostic predictors after hemispherectomy in 170 children. Neurology 2013;80:253-60.